Coping strategies and authentic leadership: nurses’ work in 2021 during the covid-19 pandemic. - da Silva Bicalho, Cleide Straub; Figueiredo, Karla Crozeta; Lessa Beltran, Rebeca Iwankiw; Silva Pol, Thaiane Almeida; Souza, Gabrielle Porfirio (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2023)
Objective: to identify the correlation between Authentic Leadership dimensions and coping strategies used by nurses during the pandemic. Methods: this is a qualitative study, with a descriptive approach, carried out with 34 nurses working in four hospitals in Curitiba. Data were collected from July to September 2021 online, using the Lazarus and Folkman Coping Strategies Inventory and the Authentic Leadership Questionnaire. Data analysis was carried out through the domain scores of each instrument according to Brazilian validation. Results: it is noted that the Balanced Processing and Self-Awareness Dimensions present a moderate positive correlation with the Accepting Responsibility, Seeking Social Support, Problem-Solving and Positive Reappraisal variables, with the latter variable presenting a moderate positive correlation with the Internalized Moral Perspective dimension, and not observes a correlation between the Relational Transparency dimension and coping strategy variables. Conclusion and implications for practice: the study demonstrates that the identified correlations encourage the team in circumstances of exhaustion, promoting a balanced cognitive behavior in the conduct of services. It is observed that the correlation between coping strategies and Authentic Leadership in the nursing area allows for the team’s engagement, credibility and self-development.